Sport and international politics - Arnaud, Pierre, 1942-; Riordan, James, 1936-2012 (E & FN Spon, 1998)
Examines the shaping of sports by both the fascist and communist institutions of Europe during the interwar period. It shows how sports were used as an instrument of propaganda and psychological pressure by major political and sporting nations.